Online Assessment during Covid-19 Pandemic: EFL Teachers’ Perspectives and Their Practices - Yulianto, Dedy; Majid Mujtahid, Nito (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
The Covid-19 pandemic made a change in learning activities from face-to-face into online distance learning. Meanwhile, teachers need to evaluate student achievements weekly even during the Covid-19 pandemic. This study aims to find out about teachers’ perspectives and their practices on the use of online assessment during Covid-19 in the context of ELT classroom. A case study design was used to answer the purpose of this research. An open-ended questionnaire and online interviews were performed to collect the data. This study revealed the teachers had a negative perception about online assessment during the Covid-19 pandemic. They got some obstacles while conducting the assessment test such as (1) the internet connection; (2) the validity of the assessment; (3) and the low of students’ enthusiasm. However, in practice, during Covid-19, the use of online assessment helps the teachers in distributing the material and assessing students’ achievement. Implications for perception and practice are also discussed.